2023
DOI: 10.3390/ijms24043674
|View full text |Cite
|
Sign up to set email alerts
|

Basic Methods of Cell Cycle Analysis

Abstract: Cellular growth and the preparation of cells for division between two successive cell divisions is called the cell cycle. The cell cycle is divided into several phases; the length of these particular cell cycle phases is an important characteristic of cell life. The progression of cells through these phases is a highly orchestrated process governed by endogenous and exogenous factors. For the elucidation of the role of these factors, including pathological aspects, various methods have been developed. Among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 106 publications
0
30
0
Order By: Relevance
“…Analysis of DNA content is among the versatile approaches used to detect cell-cycle phases . In this study, we also employed the same detection procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of DNA content is among the versatile approaches used to detect cell-cycle phases . In this study, we also employed the same detection procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the DNA content of cells is analyzed using DNA binding dyes such as propidium iodide (PI) followed by fixation of cells . Since PI also stains RNA, PI-based protocols also include the process of treating cells with RNase . Since G2- and M-phases have identical DNA contents, they could not be distinguished by differences in the DNA content.…”
Section: Methodsmentioning
confidence: 99%
“…Authors observed a delay between senescence entry and SA-β-gal derived staining [ 74 ]. Moreover, the activity of endogenous SA-β-gal is also observed in confluent non-transformed fibroblast cultures [ 73 , 75 ]. All these studies suggest that SA-β-gal as a biomarker for cellular senescence is lacking in specificity and sensitivity.…”
Section: Cellular Aging Biomarkersmentioning
confidence: 99%
“…This study can be univariate, which is often based on measuring the DNA content of cells alone, or multivariate (multiparameter), when DNA content is evaluated together with another cell feature [167]. The single time-point measurement provides information on different proportion of cells in G1, S, and G2/M [5], but not on the kinetics of the cell cycle [168]. Cells are stained with the help of DNA dye in the first approach for studying the cell cycle, and the cells' fluorescence is then measured.…”
Section: Cell Cycle Analysismentioning
confidence: 99%